Melatonin protects oocytes from cadmium exposure-induced meiosis defects by changing epigenetic modification and enhancing mitochondrial morphology in the mouse - Jingwen Qu; Qiang Wang; Haoyuan Niu; Xiaomei Sun; Dejun Ji; Yongjun Li (Ecotoxicology and Environmental Safety, 2022)
Cadmium (Cd) is one major environmental pollutant that can cause detrimental impacts on human as well as animal reproductive systems as a result of oxidative stress. It is widely acknowledged that melatonin secreted principally by the pineal gland is not only a natural potent antioxidant but also a free radical scavenger, whereas concerning how to alleviate the toxic effects of Cd on oocyte maturation remains elusive. In this investigation, it was the first time to explore the protective effects and potential mechanism of melatonin on meiotic maturation of mouse oocytes exposed to Cd in vitro medium. We found that Cd exerts adverse effects on meiotic maturation progression by disrupting the normal function of mitochondrion combined with the aberrant mitochondrial distribution and decreased membrane potential and altering epigenetic modification, including H3K9me2 and H3K4me2. Additionally, it was observed that Cd exposure disrupted the morphology of spindle organization and caused chromosome misalignment, which might be through changing the level of acetylated tubulin, whereas melatonin administration alleviated the toxic impacts of Cd on oocytes. Furthermore, the mitochondrial morphology-related genes mRNA expression and protein expression of autophagy-related genes was also investigated. The results suggested that melatonin supplementation significantly altered the mRNA expression of mitochondrial dynamics-related genes, rather than the expression of mitophagy-related proteins. Taken together, our results validated that melatonin administration has a certain protective impact against oocytes meiosis maturation defects induced by cadmium through changing epigenetic modification and enhancing mitochondrial morphology rather than mitophagy.